Manajemen Sarana Prasarana Dalam Perspektif Pendidikan Islam Untuk Meningkatkan Kualitas Pembelajaran: Studi Kasus SDIT Mutiara Insani - Siti Khotimah; Retno Wahyuningsih (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2026)
Facilities and infrastructure management is one of the strategic factors in improving the quality of learning in Islamic schools; however, its implementation still faces various challenges, particularly related to the equitable distribution and optimal utilization of learning facilities. These conditions require well planned, participatory, and sustainable management to support the achievement of educational objectives. This study aims to analyze facilities and infrastructure management in improving learning quality at SDIT Mutiara Insani. This study used a case study design and a qualitative methodology. In-depth inter views, direct observations, and documentation were used togather data, which were subsequently subjected to descriptive qualitative analytic methods. The findings indicate that facilities and infrastructure management at SDIT Mutiara Insani has been implemented through participatory planning, relatively optimal utilization of learning facilities and continuous evaluation of facilities and infrastructure. Learning facilities such as instructional media, a science laboratory and a school library contribute positively to enhancing students engagement and under standing during the learning process. Never the less, the study also reveals limitations in technology based facilities and other supporting infrastructure that have not been evenly distributed. This study concludes that well planned and sustainable facilities and infrastructure management plays an important role in improving learning quality in Islamic schools. The findings imply the need to strengthen strategies for equitable distribution of learning facilities and to optimize the utilization of existing infrastructure. Further more, future research is recommended to involve more educational institutions and to apply quantitative or mixed method approaches in order to obtain a more comprehensive understanding of facilities and infrastructure management in improving educational quality. Kata Kunci: Pengelolaan Pembelajaran, Berbasis Alam, PKBM   Kata Kunci: Educational management, facilities and infrastructure, learning quality, Islamic schools